Neurology pioneers in Japan - Hélio A. Ghizoni Teive; Léo Coutinho; Francisco E. C. Cardoso; Shoji Tsuji (Arquivos de Neuro-Psiquiatria)
The pioneers of neurology in Japan were professors Hiroshi Kawahara and Kinnosuke Miura. Kawahara published the first description of progressive bulbar palsy and wrote the first neurology textbook in Japan. Miura, on the other hand, published studies about amyotrophic lateral sclerosis, in addition to participating in the founding of the Japanese Society of Neurology. The influence of European neurology, particularly French and German, in the figures of Professor Jean-Martin Charcot and Professor Erwin Bälz, was fundamental in the consolidation of neurology in Japan.